2020
DOI: 10.3390/ani10081304
|View full text |Cite
|
Sign up to set email alerts
|

Association between Attitude and Empathy with the Quality of Human-Livestock Interactions

Abstract: The human-animal interactions are a key component of human and animal welfare. The quality of this interaction can therefore be assessed by measuring the reaction response of the animals to the handler’s behavior. The aim of this study was to investigate the association between attitude and empathy towards the animals with the quality of human-livestock interactions. Additionally, we aimed to investigate whether the quality of cattle handling deteriorates as the working day progresses. A total of 18 livestock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Research conducted in Mexico found that the education and age of transporters did not affect their perception of animal welfare, suggesting that it is likely that daily experiences during transport mean that drivers are confronted with situations of animal suffering and that their response to pain is more associated with their empathy and attitude toward animals ( 29 ). Similar results were reported in cattle handlers in Colombian cattle markets ( 32 ) and on Brazilian farms ( 33 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Research conducted in Mexico found that the education and age of transporters did not affect their perception of animal welfare, suggesting that it is likely that daily experiences during transport mean that drivers are confronted with situations of animal suffering and that their response to pain is more associated with their empathy and attitude toward animals ( 29 ). Similar results were reported in cattle handlers in Colombian cattle markets ( 32 ) and on Brazilian farms ( 33 ).…”
Section: Discussionsupporting
confidence: 86%
“…Likewise, other authors suggest that drivers should be aware of the effect of climatic changes on animals and how to act to avoid heat or cold stress during transport ( 26 , 30 ). Many factors have been associated with the effect of the driver on animal welfare such as: attitude and empathy toward animals ( 32 , 60 ), years of experience as a truck driver ( 29 ), work pressure and interpersonal relationships training ( 59 ), coaching and driving style, among others ( 45 ). These results suggest that understanding in greater depth the differences between drivers may further explain transportation losses, and therefore be useful to the swine industry to contract, hire, or train truck driver ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on companion and farm animals show that the way in which animals are considered, treated and cared for is strongly affected by peoples’ characteristics such as personality, attitudes, empathy and attachment levels and beliefs in animals’ mental capacities (e.g., [ 26 , 27 ]). In addition, sociodemographic variables, such as gender, age, family structure, education level and previous experiences with animals, play a role [ 8 , 12 , 13 , 28 , 29 , 30 ].…”
Section: The Multifaceted Nature Of the Human–animal Relationshipmentioning
confidence: 99%
“…The ways that humans interact with and care for animals is influenced by both genetic factors and life experience (Phillips 2009). It is likely driven by key personality traits, attitudes towards animals, industry role, job satisfaction, skill and commercialisation of production (Coleman et al 1998;Wilkie 2005;Hemsworth and Coleman 2011;Munoz et al 2019;Leon et al 2020;Willis et al 2021). Assessing these aspects of human psychology may provide a valid indicator of handling quality and animal care more broadly.…”
Section: Validitymentioning
confidence: 99%
“…We propose to trial the use of a suite of questionnaires adapted from other research as a proxy measure to assess stockperson care. The questionnaires will incorporate the assessment of trait sympathy (Lee 2009), attitudes towards cattle and job satisfaction (Munoz et al 2019;Leon et al 2020), pain assessment (Kielland et al 2010), disease awareness, treatment urgency and acceptability of a common welfare intervention (low stress stock handling; Nielsen 1994). Such a broad suite of questionnaires has the potential to address an aspect of welfare that is valued by consumer and community stakeholders in a way that is feasible for producers, if they are shown to be valid and reliable proxies for livestock welfare outcomes.…”
Section: Measuring Stockperson Care Through Questionnairesmentioning
confidence: 99%